2009
DOI: 10.1001/archdermatol.2008.592
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Erythematosus Tumidus

Abstract: To determine the efficacy of antimalarial drug use in patients with lupus erythematosus tumidus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 19 publications
0
18
1
1
Order By: Relevance
“…Additionally, this study found that CLE patients that smoke and require an immunomodulator in addition to antimalarial treatment are more refractory to this combination of treatment. In contrast to prior work [1012], the study found that current smokers, when they did respond to antimalarials, had a better response to monotherapy with antimalarials than never and past smokers, indicating the need to further investigate the dose-dependence between cigarette smoking and CLE disease severity and response to antimalarials. Additionally, building upon prior studies suggesting that smoking is associated with CLE in general [13], here, individuals in the CLE-only group had a higher percentage of current smokers than did the SLE with skin involvement group, suggesting that smoking may be more closely associated with CLE than SLE.…”
Section: Cutaneous Lupus Erythematous Risk Factorscontrasting
confidence: 97%
“…Additionally, this study found that CLE patients that smoke and require an immunomodulator in addition to antimalarial treatment are more refractory to this combination of treatment. In contrast to prior work [1012], the study found that current smokers, when they did respond to antimalarials, had a better response to monotherapy with antimalarials than never and past smokers, indicating the need to further investigate the dose-dependence between cigarette smoking and CLE disease severity and response to antimalarials. Additionally, building upon prior studies suggesting that smoking is associated with CLE in general [13], here, individuals in the CLE-only group had a higher percentage of current smokers than did the SLE with skin involvement group, suggesting that smoking may be more closely associated with CLE than SLE.…”
Section: Cutaneous Lupus Erythematous Risk Factorscontrasting
confidence: 97%
“…Up to 78% to 80% of patients with LET are smokers, which is significantly higher than age-matched controls, in which approximately 25% to 36% of the population are smokers 10, 11. Smokers with cutaneous lupus erythematosus do not respond as well to antimalarial therapy as do nonsmokers 10 . Although no studies have looked at the effect of smoking cessation on LET clearance, Kreuter et al 10 noted that 13 patients who quit or reduced smoking within the period of their study had complete clearance of their skin lesions.…”
Section: Discussionmentioning
confidence: 82%
“…The role of smoking has been explored in several case series. Up to 78% to 80% of patients with LET are smokers, which is significantly higher than age-matched controls, in which approximately 25% to 36% of the population are smokers 10, 11. Smokers with cutaneous lupus erythematosus do not respond as well to antimalarial therapy as do nonsmokers 10 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations